Which exercise modality is most effective for improving cardiac function in patients with myocardial infarction? A network meta-analysis - Yu, Bo; Zhao, Linlin; Huang, Liangyi; Zhang, Maolin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to compare the efficacy of different exercise modalities on cardiac function in patients with myocardial infarction (MI), providing evidence-based recommendations for optimal cardiac rehabilitation programming.MethodsWe conducted a systematic search of seven Chinese and English databases, including CNKI and Web of Science, to identify eligible studies. A network meta-analysis based on the frequency framework was performed using STATA 14.0.ResultsA total of 69 studies involving 5,044 participants were included. Compared to the control group, all exercise interventions significantly improved 6-minute walk test (6MWT) scores in MI patients, with mean differences (MDs) and 95% confidence intervals (CIs) ranging from 57.61 (34.87, 80.36) for aerobic exercise (AE) to 144.38 (110.78, 177.98) for resistance exercise (RE). All modalities enhanced left ventricular ejection fraction (LVEF), with MDs (95% CI) from 4.75 (3.42, 6.09) for AE to 8.75 (5.72, 11.77) for RE. Except for AE, all interventions reduced left ventricular end-diastolic diameter (LVEDD), with MDs (95% CI) from −4.01 (−6.42, −1.59) for multi-component exercise training (MCET) to −6.40 (−9.24, −3.56) for RE. All exercises improved left ventricular end-systolic diameter (LVESD), with MDs (95% CI) from −1.89 (−3.27, −0.51) for AE to −7.33 (−9.62, −5.03) for RE. RE consistently showed a high probability of relatively high efficacy rankings across outcomes (SUCRA: 93.2–99.8).ConclusionRE appeared to have a high probability of being a highly effective single modality for improving post-MI cardiac function and remodeling. MCET and mind-body training also offer notable advantages, particularly in reducing ventricular size. Ultimately, rehabilitation programs should be tailored by considering the modality-specific benefits, patient's clinical profile, and functional capacity to optimize outcomes.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-11-0016/, identifier INPLASY2024110016.